2015
DOI: 10.1097/adm.0000000000000165
|View full text |Cite
|
Sign up to set email alerts
|

The Adverse Effects of Motherhood on Substance Use Treatment Program Outcomes Among Adolescent Women

Abstract: Childbirth and parenting adversely affect substance use treatment outcomes for adolescent women in the criminal justice system. Future research should explore tailored substance use treatments for adolescents with children. Job training and educational support may improve outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…Conversely, negative associations occur between motherhood and SUD recovery as women get overwhelmed by children's needs. 31 The women seemed to be aided by support and emotional connection from family members, but needed to focus on meeting their own emotional and physical needs during early stages of recovery. It is possible, that at times, the women accessed more controlling regulations (such as guilt), rather than autonomous self-regulation resulting in unsatisfying experiences and behaviors, but further study is needed to understand this.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, negative associations occur between motherhood and SUD recovery as women get overwhelmed by children's needs. 31 The women seemed to be aided by support and emotional connection from family members, but needed to focus on meeting their own emotional and physical needs during early stages of recovery. It is possible, that at times, the women accessed more controlling regulations (such as guilt), rather than autonomous self-regulation resulting in unsatisfying experiences and behaviors, but further study is needed to understand this.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the studies that examined the effects of key demographic, social, and substance use constructs provided the most conclusive evidence. These studies consistently found that diversion programming did not improve outcomes among individuals who were male, frequent drug users, members of racial and ethnic minority groups, had lower educational attainment, or experienced a lack of social stability (Broussard, 2012;Butzin et al, 2002;Clark et al, 2013;Kretschmar et al, 2016;Savage et al, 2015). A few studies showed that participant treatment completion was associated with positive outcomes (Evans et al, 2009;Mendoza et al, 2018;Patra et al, 2010), but many programs struggled with maintaining participant involvement in treatment over time.…”
Section: Discussionmentioning
confidence: 99%
“…Women with substance use disorders are less likely to enter treatment than men ( 14 , 15 ). This is often due to a lack of services tailored to accommodate mothers and their children or the absence of specialist services, particularly in rural regions ( 115 , 116 ). Furthermore, most women in need of treatment feel they don't need it ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%